2019
DOI: 10.1590/0037-8682-0061-2019
|View full text |Cite
|
Sign up to set email alerts
|

Synanthropic triatomines (Hemiptera: Reduviidae): infestation, colonization, and natural infection by trypanosomatids in the State of Rio Grande do Norte, Brazil

Abstract: Introduction: The ecoepidemiological situation in the State of Rio Grande do Norte, Brazil is characterized by frequent invasion and colonization of domiciliary units (DUs) by several triatomine species, with high rates of natural infection by Trypanosoma cruzi. Methods: We evaluated the possibility of vector transmission of T. cruzi based on records of the occurrence of domiciled triatomines collected by the Secretariat of State for Public Health from 2005 to 2015. During this period, 67.7% (113/167) of munic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…The high prevalence of natural infection in T. brasiliensis populations has been shown by several authors (Alencar 1987;Costa et al, 1998Costa et al, , 2003Bezerra et al, 2018), which seems to be much higher for the state of Rio Grande do Norte (Almeida et al, 2016;Lilioso et al, 2017;Barbosa-Silva et al, 2019). Our results support the idea that TcI is the predominant genotype in anthropic environments whereas TcII/TcIV and TcIII are preferentially sylvatic.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The high prevalence of natural infection in T. brasiliensis populations has been shown by several authors (Alencar 1987;Costa et al, 1998Costa et al, , 2003Bezerra et al, 2018), which seems to be much higher for the state of Rio Grande do Norte (Almeida et al, 2016;Lilioso et al, 2017;Barbosa-Silva et al, 2019). Our results support the idea that TcI is the predominant genotype in anthropic environments whereas TcII/TcIV and TcIII are preferentially sylvatic.…”
Section: Discussionsupporting
confidence: 89%
“…They differ greatly in epidemiological terms: whereas T. brasiliensis occupies a variety of ecotopes -sylvatic, peridomestic and domestic (Costa et al, 1998(Costa et al, , 2003 -T. petrocchiae is rarely found in the peridomestic and domestic habitats, being considered exclusively sylvatic (Lent and Wygodzinsky, 1979). However, this species occasionally invades domiciles (Costa et al, 2003;Barbosa-Silva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that this high prevalence of natural infection is combined with high populational densities of T. brasiliensis in this state if compared to Paraíba [8]. These findings were confirmed by several authors throughout multiples approaches [23,43,44,45,46,47]. Noteworthy, even the populations that fed on cavies were not highly infected in Paraíba state.…”
Section: Discussionsupporting
confidence: 67%
“…The species T. pseudomaculata was the second-most collected in the Guaribas Valley territory, found in seven of the 16 studied municipalities, predominantly in the peridomiciles. This species is commonly reported in entomological surveys in the northeast region of Brazil 18,19 , including in the state of Piauí 9 . Although usually found mainly in the peridomicile 9,19 and described as feeding on birds 20 , recent investigations have reported T. pseudomaculata inside houses and feeding on human blood in central Brazil, indicating the potential of this species for intradomicile colonization and T. cruzi transmission 21 .…”
Section: Discussionmentioning
confidence: 92%
“…The species P. lutzi and T. sordida , which have both been previously reported in the state of Piauí 9 , were also collected in the study area. Panstrongylus lutzi is frequently found in the northeastern region of Brazil 18 , 19 , 22 and presents greater importance as a T. cruzi vector because it can be found in the intradomicile and present high levels of natural infections 22 , 23 . In contrast, T. sordida is typical of the cerrado biome (central region of Brazil) and occurs in the northeast region mainly in areas bordering that biome with the caatinga 14 .…”
Section: Discussionmentioning
confidence: 99%